2019
DOI: 10.1101/688820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue-specific changes in size and shape of the ligaments and tendons of the porcine knee during post-natal growth

Abstract: 23Prior studies have analyzed growth of musculoskeletal tissues between species or 24 across body segments; however, little research has assessed the differences in similar 25 tissues within a single joint. Here we studied changes in the length and cross-sectional 26 area of four ligaments and tendons, (anterior cruciate ligament, patellar tendon, medial 27 collateral ligament, lateral collateral ligament) in the tibiofemoral joint of female 28Yorkshire pigs through high-field magnetic resonance imaging throug… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The median T2* relaxation time was calculated for each ACL bundle. Additionally, the volume of each segmented tissue was recorded, and the cross-sectional area (CSA) of the AM and PL bundles, the complete ACL, MCL, and LCL were calculated as previously described (17,18).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The median T2* relaxation time was calculated for each ACL bundle. Additionally, the volume of each segmented tissue was recorded, and the cross-sectional area (CSA) of the AM and PL bundles, the complete ACL, MCL, and LCL were calculated as previously described (17,18).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Specifically, a study in adult patients reported similar joint stability after isolated AM and PL bundle injuries (11), while a study in pediatric patients reported better outcomes for AM bundle injuries (16). Furthermore, in a skeletally immature pig model, the biomechanical function of the AM and PL bundles of the ACL depends on age and sex, such that the AM bundle plays a larger functional role in older versus younger subjects and males compared to females (17,18). Since evidence regarding treatment of bundle-specific partial injuries in children and adolescents is sparse, there is a need for further investigation of long-term outcomes and degenerative changes in skeletally immature subjects.…”
Section: Introductionmentioning
confidence: 99%